Evaluation of quality-related indexes in National Clinical Research Network Centers - Ilana, Gabriela Gimenez Faustino; Cintra, Monica Akissue de C Teixeira; Costa, André Lucirton; Coelho, Eduardo Barbosa (Medicina (Ribeirao Preto), 2018)
Study design: A transversal study that evaluated 32 Clinical research centers (CRC) of the National Clinical Research Network (Rede Nacional de Pesquisa Clínica/RNPC). Objectives: To develop and validate an electronic questionnaire to measure how CRC that are part of the RNPC performed in a quality audit based in Good Clinical Practice, to evaluate the correlation between our instrument and IN4/ANVISA guide and to access the quality of the CRC. Methods: An electronic questionnaire was applied and validated by contend valid index. The questions were divided into tree domains, infrastructure (I), organization structure (OS) and process (P). Data were scored according compliance (1) or non-compliance (0) with GCP. The questions of our questionnaires where arbitrary related to IN4/ANVISA guide and scored as non-conformity (1) or conformity (0). The indexes of compliance in critical and major items (ICCM) were calculated using the equation: ICCM = 1 * (IN4 score) + total score for the domain. The correlation of the two measurements above was done using Kruskal-Wallis and Spearman rank method, considering P <0.05. Results: The questionnaire represents about 40% of the IN/ANVISA document. The score obtained with the questionnaire had a significant correlation to IN4/ ANVISA score (r=0.95, 0.89 to 0.98, CI95%, P<0.0001). The median ICCM was less than 75% for all domain studied. Conclusion: The instrument designed to measure performance GCP showed high correlation with IN4/ ANVISA guide and could be used to perform the internal quality audit of a CRC. The IN4/ANVISA guide showed to be very strict and might be necessary to review it and adequate to the reality of nationals centers.